Foreign employment and economic growth in Malaysia / Mohd Izli Zainol - Zainol, Mohd Izli (Faculty of Business and Management, 2008)
According to Ministry of Finance Malaysia, the foreign workers have contributed to the economic growth of the country, in particular by alleviating labor shortages in selected sectors of the economy. However, their presence has also put stress on public amenities and services, such as the provision of public services, health and education facilities. Remittances by foreign workers have also increased steadily as reflected in the outflow of the current transfers in the country's balance of payments. In 2003, the account recorded gross outflow of RM11, 229 million compared to RM6, 957 million recorded in 1997. (Economic Report 2004/2005) This study generally is conducting to identify the relationship between foreign employment and economic growth in Malaysia. This study specifically focuses on the effects of Worker's remittance, Compensation of Employees and Migrant Transfers and also the other variables to the economic development in Malaysia. For this study, secondary data have been used as data collection and data that has been used is from 2000 to 2007 in quarterly basis. For the finding of this study, regression analysis has been used as method to analyze the data. The finding in this study also has been used to answer the hypotheses and make conclusion with several recommendations.